2021
DOI: 10.1101/2021.01.08.425986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explosive diversification following continental colonizations by canids

Abstract: Colonization of a new environment may trigger an explosive radiation process, defined as an accelerated accumulation of species in a short period of time. However, how often colonization events trigger explosive radiations is still an open question. We studied the worldwide dispersal of the subfamily Caninae, to investigate whether the invasion of new continents resulted in explosive radiations. We used a combination of phylogenetic analyses and ancestral area reconstructions to estimate ancestral ranges of 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…These explanations assume that clustered communities undergo mostly sympatric speciation whereas overdispersed communities assembled through immigration after allopatric speciation. This seems to be in line with the results from Porto et al (2021), on the origin and dispersal of the Canidae lineages. They show that highly clustered communities, such as the Middle East and South America, present several lineages that originated within these regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These explanations assume that clustered communities undergo mostly sympatric speciation whereas overdispersed communities assembled through immigration after allopatric speciation. This seems to be in line with the results from Porto et al (2021), on the origin and dispersal of the Canidae lineages. They show that highly clustered communities, such as the Middle East and South America, present several lineages that originated within these regions.…”
Section: Discussionsupporting
confidence: 91%
“…Even though canids are not very dispersal limited, because they can travel long distances (Wang and Tedford 2008, Wilson and Mittermeier 2009), they may still tend to be found in higher numbers near their center of diversification than far from it. This can also help to understand the phylogenetic structure of the Middle East and the southern portion of South America, which, based on the fossil records and biogeographical models, had major diversification events of foxes and South American canids, respectively (Wang and Tedford 2008, Porto et al 2021). Ecological speciation within these regions might have generated species’ phylogenetic clustering.…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of the birth (and death) of a new species, its initial (and final) geographical distribution is typically restricted, at least with respect to its maximum distribution typically attained at some time during its lifetime (Foote, 2007;Liow & Stenseth, 2007;Žliobaitė et al, 2017). Hence, the arrival of a species into a new area (e.g., Kennedy et al, 2018;Porto et al, 2021), the extinction of competitors (e.g., Silvestro et al, 2015), or the emergence of a key innovation (e.g., Matschiner et al, 2011), for example, might result in the dispersion of individuals into unoccupied areas. Given enough time, most of the available area might be occupied.…”
Section: A Heuris Ti C Inde X To Link P Opul Ation -Le Vel and Microe Volutionary Proce Ss E S To Predic T Macroe Volutionary Pat Te R N mentioning
confidence: 99%
“…More specifically, what is the role of interspecific interactions in shaping biotic communities at different spatial and temporal scales (Broennimann et al, 2012; Godsoe et al, 2017; Letten et al, 2017; Segar et al, 2020; Wisz et al, 2013)? Several studies have found associations between species' geographic distributions and assemblage structure with ecological drivers such as climate, dispersal abilities, historical events and biotic interactions, acting at different scales (Arias‐Alzate et al, 2020; Blois et al, 2014; Lombardi et al, 2020; Porto et al, 2021; Santos et al, 2019; Vilella et al, 2020; Zhao et al, 2020). Nevertheless, elucidating the interactive effects of these factors on species' coexistence is challenging, and causation might not be restricted to a single factor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…carnivoran mammals) inhabiting the same geographic space can coexist only if one or more species shifts key ecological traits to ward off (i.e. character displacement; Arias‐Alzate et al, 2020; Chesson & Grubb, 1990; Hutchinson, 1978; Leibold, 1995; Mikkelson, 2005; Porto et al, 2021; Steinitz et al, 2006; Villalobos & Arita, 2014). Therefore, from a phylogenetic conservatism perspective, carnivoran assemblages will likely be phylogenetically over‐dispersed (Bianchi et al, 2016; Porto et al, 2021; Santos et al, 2019; Segar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%